The Effect of Contact Angle on Dynamics of Dry Spots Spreading in a Horizontal Layer of Liquid at Local Heating; MATEC Web of Conferences; Vol. 37 : Smart Grids 2015 - Zaitsev D. V. Dmitry Valerievich; Kirichenko D. P.; Orlik E. V. Evgeny Vladimirovich; Kabov O. A. Oleg Aleksandrovich (2015, 2015)
Title screen